Implementation of Learning Policy in SMA Negeri 1 Tulungagung during the Covid-19 Pandemic - ivan surya mahendra; Ahmad Izzul Ito’ (9 772338317006, 2022)
This study aims to determine the application of distance learning policies at SMAN1 Tulungagung schools in terms of aspects of constraints and advantages. Online learning is an open and distributed systematic learning by using pedagogical devices (educational aids) via the internet and network-based technology. user needs, for example downloading various source requirements for soldering. Online virtual learning is an alternative policy that was forced to be taken by the Indonesian government as an effort to break the distribution chain of COVID-19 in the community, especially in the school environment. which was originally mostly face-to-face learning in the context of classroom atmosphere schooling into online/online-based learning called the application of Blended Learning model learning which is often defined as an optimizing system in integrating oral communication that exists in face-to-face learning with written communication in online learning. The learning policy that is implemented, of course, all parties must work well together so that the implementation of learning restrictions becomes an effective policy so that student learning outcomes during online learning do not deny the results of face-to-face learning in classrooms as during the pre-pandemic in our country. Various positive responses were conveyed by students regarding online learning. In addition, teachers and parents also play a role in providing support and guidance to children's learning efforts.